Asas Keadilan dalam Transaksi Derivatif (Khusus yang Diperdagangkan dalam Bursa) Sebagai Objek Pengenaan Pajak Penghasilan - Kadarukmi, M.E. Retno (Jurnal Administrasi Bisnis, 2012)
Basically derivative transactions carried out for the divertion of risks that may arise,either the exchange rate risk, interest rate and stock price fluctuations. Derivativetransactions is then evolved rapidly. This increase is due to many benefits and profitsderived from derivative transactions. The benefits in the form of tools for risk man-agement and price discovery, so appear protection (hedging) of assets. The profit isincreasing the income of the. transactors. In fact, derivative transactions more oftenused to make a profit from speculative activities, not for protection (hedging). Nowthe derivative transactions are set out in the Income Tax Act, is inserted into one of theobjects of Income Tax. Income Tax imposed by the final and by some businessmenconsidered to violate the principle of justice.Keywords: Tax, Benefit, Profit, Hedging